Ikhsan Pratama - Ikhsan Pratama (Journal of Integrated Knowledge and Innovation, 2025)
The utilization of pineapple as a value-added processed product provides a strategic opportunity for the development of micro, small, and medium enterprises (MSMEs) in pineapple-producing regions. This study aims to examine product innovation of pineapple chips as a strategy for local economic empowerment in the era of creative economy. This research employed a qualitative approach using observation, interviews, and documentation techniques with pineapple chip MSME actors in Kampar Regency, Riau. The results indicate that innovation is carried out through vacuum frying, modern packaging design, and digital marketing strategies via social media. These innovations not only increase the economic value of the product but also create job opportunities and empower local farmers. Major challenges include limited capital, production capacity, and market competition. Collaboration between entrepreneurs, government, and educational institutions is necessary to ensure the sustainability of this business.